Bioethanol production from cassava feedstock a plant design - Gibas, Johanna Angelique L.; Kabigting, Nigel Joseph V.; Tolentino, Joy Christine A.
There is a large deficiency in the supply of bioethanol in the country since the implementation of the Biofuels Act of 2006; therefore, in order to help increase the supply in the country, a bioethanol plant utilizing cassava as feedstock with a capacity of 25 million liter per year will be designed, This study will include: (1) an introduction and literature review, (2) the process details like process flow diagram and process description, and plant layout, (3) detailed equipment design, and (4) an economic study to determine the profitability of the proposed plant. The bioethanol market is expected to continuously grow in the future due to the impending increase in the blend requirement and the increasing number of motor vehicles used in the country. But even with this expected stability in the market, there are still only few local producers of bioethanol whose combined capacities do not suffice to meet that demand. The bioethanol industry offers a good investment opportunity since, currently, there is no competition among local producers since the law requires the utilization of locally-produced bioethanol before importation is allowed. Raw materials are available locally but importation could also be considered. The main consideration for the site location is the availability of abundant raw material so the provinces with the highest annual yield for cassava were chosen, namely South Cotabato and Sarangani. For the process development, the feasibility study conducted by the International Society for Southeast Asian Agricultural Sciences was used as the main source. For the process synthesis, various literature were surveyed to determine the possible pathways for the reactions and separation to be performed. Selection was based on the economic and technical feasibility of the system.From the process synthesis and development performed and the mass and energy balances calculated, the process flow diagram was created. The table of steam properties the summarize the important characteristics of each of the streams involved in the process. Utilities and their properties were also listed. A summary of the mass and energy balance for the whole plant was also presented. Health, safety and environmental hazards were also considered before the plant layout was produced. The piping and instrumentation diagram the resulted from the calculations of fluid motive device requirements and from the study of required control schemes for each equipment. Lastly, a waste management system was developed to ensure the safety and accordance to disposal laws.Detailed equipment design was performed for all of the equipment needed except for some which will be purchased. The design problem, mass and energy balances, equipment specifications, hazard and operability study, and equipment cost comprise the discussion for the equipment that will be purchased. Design considerations, design methodology, component specifications, and process control scheme were topics added for those equipment that will be designed. The critical equipment in the plant are : dryer, saccharification tank, fermentation tanks, distillation column, and adsorption column. The dryer reduces the moisture content of the cassava chips. The saccharification tank converts the dextrin to glucose while the fermentation tanks produce ethanol and glucose from glucose syrup. The distillation column increases the purity of the ethanol solution to 95% while the adsorption column further increases it to 99.5%. The suggested selling price set by the Sugar Regulatory Administration is Php 46.61/L. The carbon dioxide selling price is Php 6.30/kg. When this selling price is used, the bioethanol plant will not be profitable and there would be no computed internal rate of return and discounted payback period because of the large negative net present value. If the selling price, however, is set to Php 280/L, the net present value is computed to the Php 357,025,631.76, and the computed internal rate of return is 10.24%, which is higher than the minimum attractive rate of return of 10%. Moreover, the discounted payback period is 8.06 years, which is just two years after the plant produces at a full capacity of ~27 million liters. The net present value of the bioethanol plant is most sensitive to changes is selling price, thus validating the step to change the selling price to make the investment more profitable. Based on the market study, the bioethanol industry is a promising industry for investments since a continuous increase in demand is forecasted and the supply is not enough; however, based on the profitability analysis, the proposed plant will only be profitable if the ethanol is sold at a high price.